2018
DOI: 10.3324/haematol.2017.167288
|View full text |Cite
|
Sign up to set email alerts
|

Gfi1b: a key player in the genesis and maintenance of acute myeloid leukemia and myelodysplastic syndrome

Abstract: Differentiation of hematopoietic stem cells is regulated by a concert of different transcription factors. Disturbed transcription factor function can be the basis of (pre)malignancies such as myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). Growth factor independence 1b (Gfi1b) is a repressing transcription factor regulating quiescence of hematopoietic stem cells and differentiation of erythrocytes and platelets. Here, we show that low expression of Gfi1b in blast cells is associated with an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
4
24
0
Order By: Relevance
“…Growth factor independence 1b (GFI1B) encodes a key transcription factor regulating dormancy and proliferation of hematopoietic stem cells (HSCs) and the development of erythroid and megakaryocytic cells (31,32). Recent studies had revealed its critical role as a tumor suppressor in AML, as low GFI1B expression is associated with poor patient survival (33). Consistent with previous studies, the 6 patients with GFI1B enhancer mutation have significantly shorter time to relapse ( Figure 3F).…”
Section: Risk Enhancer/promoter Snvs and Small Indelssupporting
confidence: 84%
“…Growth factor independence 1b (GFI1B) encodes a key transcription factor regulating dormancy and proliferation of hematopoietic stem cells (HSCs) and the development of erythroid and megakaryocytic cells (31,32). Recent studies had revealed its critical role as a tumor suppressor in AML, as low GFI1B expression is associated with poor patient survival (33). Consistent with previous studies, the 6 patients with GFI1B enhancer mutation have significantly shorter time to relapse ( Figure 3F).…”
Section: Risk Enhancer/promoter Snvs and Small Indelssupporting
confidence: 84%
“…However, the role of GFI1B in AML is uncertain. Despite GFI1B often being increased in AML patients (29)(30)(31)(32), a recent study suggests that low GFI1B expression correlates with poor patient outcome and that in mice, Gfi1b depletion accelerates progression to AML from myelodysplasia driven by a NUP98-HOXD13 fusion protein (33). Collectively, these observations suggest widespread contributions by GFI family proteins to lineage allocation during normal hematopoiesis and both oncogenic and oncosuppressor roles in hematologic malignancies.…”
mentioning
confidence: 99%
“…The results showed that a putative binding site of growth factor independent 1B transcriptional repressor (GFI1B) was present in the promoter region of PGM5-AS1 ( Supplementary Table S1). GFI1B is an inhibitory transcription factor that regulates the quiescence of hematopoietic stem cells and differentiation of red blood cells and platelets [26]. Plasmid (pcDNA-GFI1B) was used to overexpress GFI1B, and small interfering RNA (si-GFI1B) assisted in knocking down GFI1B ( Figure S1B).…”
Section: Resultsmentioning
confidence: 99%